Chitosan-reinforced alginate microspheres obtained through the emulsification/internal gelation technique - Ribeiro, António J. (2005)
Alginate microspheres prepared by emulsification/internal gelation were chosen as carriers for a model protein, hemoglobin (Hb). Reinforced chitosan-coated microspheres were obtained by an uninterrupted method, in order to simplify the coating process, minimize protein losses during production and to avoid Hb escape under acidic conditions. Microspheres recovery was evaluated as well as its morphology by determination of Hb encapsulation efficiency and microscopic observation, respectively. The formation of chitosan membrane made of it interaction with alginate was assessed by DSC (differential scanning calorimetry) and FT-IR (Fourier-transform infrared spectrometry) studies. Spherical uncoated microspheres with a mean diameter of 20 [mu]m and encapsulation efficiency above 89% were obtained. Coated microspheres provided similar encapsulation efficiency but a higher mean diameter was obtained due to microspheres clumping during the coating step. Protein loss occurred mainly during emulsification rather than recovery. FT-IR and DSC together indicated electrostatic interactions between alginate carboxylate and chitosan ammonium groups as the main forces for complex formation.